2023
DOI: 10.3390/plants12112221
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Kaolin and Silicon Nanoparticles for Ameliorating Deficit Irrigation Stress in Maize Plants by Upregulating Antioxidant Defense Systems

Abstract: Water deficit is a significant environmental stress that has a negative impact on plant growth and yield. In this research, the positive significance of kaolin and SiO2 nanoparticles in moderating the detrimental effects of water deficit on maize plant growth and yield is investigated. The foliar application of kaolin (3 and 6%) and SiO2 NPs (1.5 and 3 mM) solutions increased the growth and yield variables of maize plants grown under normal conditions (100% available water) and drought stress conditions (80 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Similarly, Elshayb et al (2021) in their study on rice concluded that a significant increase in SOD and CAT activity was observed in plants watered every 6 days, while the maximum POD activity in plants watered every 9 days, treated with 60 ppm SiNPs. According to Al-Mokadem et al (2023), foliar application of 3 mM SiNPs significantly increased activities of antioxidant enzymes like CAT, SOD, POX, GR, and APX of Zea mays under water deficit conditions. Similarly, the application of SiNPs increased the activities of CAT, SOD, or G-POX, except for APX, of maize plants subjected to DS (Figure 2) (Sharf-Eldin et al, 2023).…”
Section: Sinps Improve the Antioxidant Defence Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Elshayb et al (2021) in their study on rice concluded that a significant increase in SOD and CAT activity was observed in plants watered every 6 days, while the maximum POD activity in plants watered every 9 days, treated with 60 ppm SiNPs. According to Al-Mokadem et al (2023), foliar application of 3 mM SiNPs significantly increased activities of antioxidant enzymes like CAT, SOD, POX, GR, and APX of Zea mays under water deficit conditions. Similarly, the application of SiNPs increased the activities of CAT, SOD, or G-POX, except for APX, of maize plants subjected to DS (Figure 2) (Sharf-Eldin et al, 2023).…”
Section: Sinps Improve the Antioxidant Defence Systemmentioning
confidence: 99%
“…SiNPs have great potential to enhance antioxidant activity, thereby alleviating the negative effects of drought-induced stress. Utilization of SiNPs notably enhanced activities of CAT, SOD, or POD, leading to a reduction in oxidative damage of DS (El-Beltagi and Mohamed, 2010;Afify et al, 2011;Afify et al, 2012;Al-Mokadem et al, 2023;Elshayb et al, 2021;Pinedo-Guerrero et al, 2020;Sutulienė et al, 2021). Raza et al (2023) reported that the treatment of SiNPs on wheat plants resulted in improved antioxidant enzyme activities.…”
Section: Sinps Improve the Antioxidant Defence Systemmentioning
confidence: 99%
“…Several strategies have been implemented to overcome the hazardous effects of drought on wheat. Biopriming is one of the plants’ most well-known methods for reducing drought stress [ 13 ]. Hydropriming, osmo-priming, hormone priming, solid matrix, thermos-priming, nutria-priming, chemo-priming, and biological priming were all documented methods of priming [ 14 ].…”
Section: Introductionmentioning
confidence: 99%